The relation between blood and tissue magnesium levels and development of atrial fibrillation after coronary artery bypass surgery - BİLĞİÇ ALKAYA, DİLEK (TURKISH SOC CARDIOLOGY, 2010)
Objective: Atrial fibrillation (AF) is a common complication of cardiovascular surgery and its mechanisms are not well understood. The aim of our study was a prospective investigation of the relationship between AF development and tissue or blood magnesium levels. Methods: This prospective observational study evaluated 20 patients undergoing elective initial coronary artery bypass graft (CABG) surgery. Right atrial appendage and skeletal muscle samples were obtained for tissue magnesium level analysis before, during (at 60(th) minute) and 30 minutes after cardiopulmonary bypass (CPB) with simultaneous blood samples. Daily measurements of blood Mg levels and continuous monitoring for AF were performed for 7 postoperative days. Statistical analyses were performed using ANOVA, independent samples t and Chi-square tests. Results: AF developed in 5 out of 20 patients during postoperative period (25%). Patients with or without AF did not differ in terms of tissue and blood magnesium levels during and early after CPB and during 7 days after the operation. Blood magnesium levels were significantly higher in the whole study population on postoperative days 3 through 7 (day 3 - 1.13 +/- 0.11 mmol/L; day 4-, 1.18 +/- 0.07 mmol/L; day 5-1.15 +/- 0.10 mmol/L; day 6-1.17 +/- 0.08 mmol/L; and day 7, 1.22 +/- 0.08 mmol/L) compared to day 1 and day 2 (day 1-0.96 +/- 0.13 mmol/L and day 2-1.02 +/- 0.12 mmol/L; p<0.002 for all comparisons). Conclusion: Although patients with and without AF did not significantly differ with regard to blood and tissue magnesium levels, the coincidence of an early postoperative reduction in magnesium levels in all patients and occurrence of all AF incidences at this time period suggests a potential association deserving further investigation. (Anadolu Kardiyol Derg 2010; 10: 446-51)
Keywords: Coronary artery bypass grafting; atrial fibrillation; tissue magnesium level; blood magnesium level